In vitro release kinetics and in vivo plasma exposure of green tea polyphenols and caffeine from iron oxide chitosan nanoparticles - Al Awawdeh, Safaa; Shafie, Nurul Husna; Ishak, Amirah Haziyah; Mohd Esa, Norhaizan; Loh, Su Peng; Nurdin, Armania (Nature Research, 2026)
Green tea polyphenols (GTPP) are known for their antioxidant and anticancer activities but suffer from low bioavailability due to instability in the gastrointestinal environment. This study aimed to enhance the oral delivery of GTPP by encapsulating epicatechin, epigallocatechin gallate (EGCG), catechin, gallic acid, theaflavin, and caffeine into iron oxide chitosan nanoparticles (IOCHNP). Using high performance liquid chromatography (HPLC), the release of GTPP was evaluated in vitro and in vivo in both simulated intestinal media and rat’s plasma. GTPP-IOCHNP efficiently encapsulates GTPP, achieving an encapsulation efficiency of 90.9% for catechin and 83.3% for theaflavin. Additionally, less than 8% of GTPP is released in simulated gastric fluid (SGF), while its more readily released in simulated intestinal fluid (SIF) is enhanced, reaching 70% for caffeine. The release of gallic acid and epicatechin followed Higuchi kinetics, catechin followed Korsmeyer-Peppas, and caffeine followed Weibull model, indicating diverse mechanisms of release. The in vivo results demonstrated that GTPP loaded GTPP-IOCHNP significantly enhanced the absorption of GTPP compared to GTPP administered alone (p < 0.05). The bioavailability of EGCG, epicatechin, catechin, gallic acid and theaflavin was improved by approximately 8.5-, 6.5-, 4.8-, 5- and 3.5- fold respectively when delivered using GTPP-IOCHNP as a carrier. These findings highlight the potential of IOCHNP as an efficient oral delivery platform for tea polyphenols.